1998
DOI: 10.1007/pl00009544
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic Endoscopic Evaluation of Dysphagia to Identify Silent Aspiration

Abstract: The traditional bedside dysphagia evaluation has not been able to identify silent aspiration because the pharyngeal phase of swallowing could not be objectively assessed. To date, only videofluoroscopy has been used to detect silent aspiration. This investigation assessed the aspiration status of 400 consecutive, at risk subjects by fiberoptic endoscopic evaluation of swallowing (FEES). Our study demonstrated that 175 of 400 (44%) subjects were without aspiration, 115 of 400 (29%) exhibited aspiration with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
1
24

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(164 citation statements)
references
References 13 publications
5
134
1
24
Order By: Relevance
“…FEES is particularly suited to the burn population and may be the preferred procedure during the acute phase following burn injury due to its ability to assess sensory impairment, edema, erythema and ulceration of pharyngeal and laryngeal structures caused by concomitant inhalation injury, and its ability to be carried out at bedside when mobility and positioning are compromised by pain, splints and contractures 11 . Furthermore, FEES is repeatable, which caters for the long recovery process for burn patients and allows for assessment of vocal cord integrity and function, which can be affected by endotracheal intubation and inhalation injury 53 .…”
Section: Resultsmentioning
confidence: 99%
“…FEES is particularly suited to the burn population and may be the preferred procedure during the acute phase following burn injury due to its ability to assess sensory impairment, edema, erythema and ulceration of pharyngeal and laryngeal structures caused by concomitant inhalation injury, and its ability to be carried out at bedside when mobility and positioning are compromised by pain, splints and contractures 11 . Furthermore, FEES is repeatable, which caters for the long recovery process for burn patients and allows for assessment of vocal cord integrity and function, which can be affected by endotracheal intubation and inhalation injury 53 .…”
Section: Resultsmentioning
confidence: 99%
“…The identification of aspiration is critical to rehabilitation planning for the individual with dysphagia. Numerous aspiration detection technologies along with accompanying clinical screening procedures have been proposed in the literature (see [1] for a review), including, for example, fiberoptic endoscopy [12], pulse oximetry [13], electroglottography (EGG) [14], cervical auscultation with pharyngeal microphone [15], and the present-day gold standard, the modified barium swallow using videofluoroscopy [10]. There is, however, a practical need for a noninvasive, economical, and portable method for detecting aspiration [16] at the bedside and outside of the institutional setting.…”
Section: B Detection Of Aspirationmentioning
confidence: 99%
“…8 -11 Several studies showed that FEES is equal to or even better than videofluoroscopy (VF) in detecting aspiration and severity of residues. [12][13][14][15][16] Preliminary evidence also suggests FEES guided dietary and behavioral management to result in a better outcome of acute stroke patients compared to a management guided by VF. 13 Moreover, in the acute care of stroke patients, FEES has the advantages that it can be performed at bedside, is repeatable as often as necessary, allows evaluation of both the motor and sensory component of swallowing, and permits assessment of airway protection.…”
mentioning
confidence: 99%